Menemukan Haji Hasan Mustafa (1852-1930) - Jajang Jahroni (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2018)
Julian Millie (ed.). 2017. Hasan Mustapa: Ethnicity and Islam in Indonesia. Melbourne: Monash University Publishing.Despite Haji Hasan Mustafa left many scholarly works, his name is almost unheard among scholars interested in Sundanese studies. It has been argued that this fact is related to the nature of his works, mostly written in Sundanese language and on Islamic mysticism, which are hardly understandable to his successors. Studies on Mustafa began to arise in the 1960s when Ajip Rosidi, one of the most Sundanese writer, published his work on him. But it did not attract public enthusiasm. In spite of this, Rosidi’s work inspired many young scholars who have the similar concern that this idiosyncratic figure deserved to be widely introduced to the public. One of this scholars is Julian Millie who has extensive research on Sundanese culture. It is no doubt that this book sparks a new horizon on Sundanese culture, particularly the relation between Sundanese culture and Islam.DOI: 10.15408/sdi.v25i2.8974